2014
DOI: 10.1111/ejn.12563
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐modal decoupling in temporal attention

Abstract: Prior studies have repeatedly reported behavioural benefits to events occurring at attended, compared to unattended, points in time. It has been suggested that, as for spatial orienting, temporal orienting of attention spreads across sensory modalities in a synergistic fashion. However, the consequences of cross-modal temporal orienting of attention remain poorly understood. One challenge is that the passage of time leads to an increase in event predictability throughout a trial, thus making it difficult to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 73 publications
3
33
3
Order By: Relevance
“…Moreover, parallels can also be drawn to a study where participants were cued to expect either a visual or tactile target at a specific time point. Mühlberg, Oriolo, and Soto-Faraco (2014) showed that attending to one modality did not benefit the second, unattended modality, at the expected time point. That is, endogenous temporal attention can be deployed relatively independently across modalities (c.f.…”
mentioning
confidence: 91%
“…Moreover, parallels can also be drawn to a study where participants were cued to expect either a visual or tactile target at a specific time point. Mühlberg, Oriolo, and Soto-Faraco (2014) showed that attending to one modality did not benefit the second, unattended modality, at the expected time point. That is, endogenous temporal attention can be deployed relatively independently across modalities (c.f.…”
mentioning
confidence: 91%
“…Instead, most targets presented at the unexpected time point belonged to the secondary, less frequent, modality. Hence, Lange and Röder's experiment design (followed by Mühlberg et al's 2014, and the present study) used a probabilistic manipulation, with the general assumption that manipulations of expectancy can induce corresponding orienting of top-down attention (see Correa et al, 2005;Nobre & Rohenkohl, 2014). Attention and expectation are technically dissociable processes, with different expressions in terms of brain correlates Summerfield & Egner, 2009), but have hardly distinguishable behavioural outcomes.…”
mentioning
confidence: 97%
“…Driver & Spence, 1994;Eimer & Driver, 2000;Eimer et al, 2002;Eimer, 1999;Macaluso & Driver, 2005;Macaluso et al, 2000;Macaluso, 2010;Sambo & Forster, 2011;Santangelo et al, 2010;Spence & Driver, 1997, 1996Spence et al, 2000;Tang et al, 2015;Trenner et al, 2008). However, in contrast to spatial attention, the consequences of cross-modal orienting in time have been far less studied and the interpretation of the results is still controversial Mühlberg et al, 2014). conducted a relevant study that addresses the question of orienting temporal attention in a cross-modal environment.…”
mentioning
confidence: 99%
“…Prior research has also shown that the effect of temporal expectation can be either modality-specific (facilitation at the expected time only for a behavioral target in the expected modality) or modality-independent (facilitation at the expected time for a behavioral target in either an expected or an unexpected modality), depending on the pairing of sensory modalities and other stimulus factors (e.g., Mühlberg et al, 2014). However, no prior study has investigated how temporal expectation might influence crossmodal interactions using multimodal stimuli, despite the fact that crossmodal integration crucially depends on timing (e.g., Holmes & Spence, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that temporal expectation facilitates perceptual processing independently of modality. However, using a similar experimental design with visual and tactile stimuli, Mühlberg, Oriolo, and Soto-Faraco (2014) showed that, whereas the processing of stimuli in the expected modality benefited from occurring at the expected time, as indicated by faster responses, the processing of stimuli in the unexpected modality did not. This result suggests that temporal expectation facilitates perceptual processing in a modality-specific manner.…”
Section: Congruity Effectmentioning
confidence: 97%